COMPARATIVE STUDY OF PARTICLEBOARDS WITH HEVEA BRASILIENSIS WASTE FROM DIFFERENT PRODUCTION AND MOISTURE CONFIGURATIONS - Souza, Matheus Viana de [UNESP]; Cazella, Pedro Henrique da silva [UNESP]; Da Silva, Sergio Augusto Mello [UNESP]; Rodrigues, Felipe Reis [UNESP]; Herradon, Marjorie Perosso [UNESP]; Da Costa, Fabiola Medeiros [UNESP]; Aouada, Marcia Regina De Moura [UNESP]; Aouada, Fauze Ahmad [UNESP]; Santos, Herisson Ferreira dos; Pinto, Edna Moura; Araujo, Victor Almeida de; Christoforo, Andre Luis; et al. (Slovak Forest Products Research Inst, 2022)
After the production cycle of latex, Hevea brasiliensis trees become residual living plants for this activity, although their woody trunks are still potentially subject to industrial utilization. Bio-composites derived from rubberwood particles were manufactured using two different configurations as a strategy to examine the potential of this species with respect to mechanical behavior. Homogeneous panels were developed from particles at the saturation condition, and heterogeneous panels were obtained from dry particles conditioned at 12% moisture content. Both examples were heat-pressed and glued with castor oil-based polyurethane resin. Density, short-term water absorption and thickness swelling, modulus of rupture and modulus of elasticity in the static bending and perpendicular tensile were evaluated. Panels derived from rubberwood particles proved to be viable according to the technical standards.
Keywords: Rubberwood; timber; castor oil-based polyurethane; sawmilling waste